1962
DOI: 10.1149/1.2425390
|View full text |Cite
|
Sign up to set email alerts
|

Physical Chemistry of Macromolecules

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
685
1
8

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 508 publications
(729 citation statements)
references
References 0 publications
35
685
1
8
Order By: Relevance
“…It is shown that the concentration dependence of each may be accounted for quantitatively over a wide concentration range by a simple model, according to which each protein molecule interacts with other protein molecules only via short-ranged repulsive interactions that may be approximated as hard particle interactions, and does not selfassociate to any significant extent over the concentration range examined. Molecular weights obtained for all three proteins agree well with literature values [4,18]. 2 We note that v eff is defined equal to the specific volume of a hard spherical particle whose interparticle interactions best mimic that of the actual protein under a particular set of experimental conditions.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…It is shown that the concentration dependence of each may be accounted for quantitatively over a wide concentration range by a simple model, according to which each protein molecule interacts with other protein molecules only via short-ranged repulsive interactions that may be approximated as hard particle interactions, and does not selfassociate to any significant extent over the concentration range examined. Molecular weights obtained for all three proteins agree well with literature values [4,18]. 2 We note that v eff is defined equal to the specific volume of a hard spherical particle whose interparticle interactions best mimic that of the actual protein under a particular set of experimental conditions.…”
Section: Discussionsupporting
confidence: 84%
“…The concentration dependence of the logarithm of the activity coefficient is obtained by modeling the protein molecule as an effective hard spherical particle [7]: (4) where φ denotes the fraction of volume occupied by protein, given by (5) and v eff is the specific volume of the effective hard spherical particle 2 . The infinite power series indicated in equation (4) is truncated after five terms since test calculations indicated convergence over the measured range of concentration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At constant temperature and viscosity, the frictional coe¤cient, f, depends on the radius and the shape of the molecule [17]. We therefore conclude that binding of nucleotides (either ATP or AMPPNP) leads to a large conformational change in the F I part of the enzyme.…”
Section: Resultsmentioning
confidence: 76%
“…7 Solutions to simple problems with spherical, cylindrical, or planar symmetry are available for the linearized PB equation. 8,9 A closedform formula for the solution of nonlinear PB does not seem to be possible except for the planar case 10 and the infinite cylindrical symmetric case, where only counterions exist in the solution. 11 In attempting to use numerical methods to solve the PB equation with complicated molecular geometries and charge distributions, a number of challenges present themselves.…”
Section: Introductionmentioning
confidence: 99%